THE EFFECT OF GROUP EDUCATION USING ONLINE MEDIA ON SELF CARE ON OBESITY STUDENTS AT THE FACULTY OF NURSING MUHAMMADIYAH UNIVERSITY JAKARTA 2021 (Jurnal Mitra Kesehatan, 2021)
Introduction: Obesity in young adults can cause various health problems, including in the long term it will cause complications of diseases such as hypertension, diabetes mellitus and death at a young age. Self care in obesity is a management consisting of diet processing, physical activity, modification of life attitude (behavior therapy) and medical therapy. Peer group education is a method that helps increase understanding and self-care for obese students. The purpose of this study was to determine the peer group education method to increase self-care of obese students. Method: The research design used was a quasi-experimental pre and post test, with a dependent t-test. Collecting data using the Diabetes Self Management Questionnaire (DMSQ). Sample of 30 respondents. Results: The results of this study obtained that there was an effect of peer group education on increasing the self-care value of obese students (p-value = 0.00). Conclusion: Suggestions from this study are self-care is one of the efforts that can be used to overcome the problem of obesity at a young age. Educational institutions can implement self-care through healthy exercise programs every morning or health education programs in health services.